2021
DOI: 10.1016/j.yexcr.2021.112854
|View full text |Cite
|
Sign up to set email alerts
|

NFATc1 promotes epithelial-mesenchymal transition and facilitates colorectal cancer metastasis by targeting SNAI1

Abstract: BackgroundMetastatic recurrence remains a major cause of colorectal cancer (CRC) mortality. In this study, we focused on the role and the potential underlying mechanisms of nuclear factor of activated T cells 1 (NFATc1) in CRC metastasis. MethodsWe examined the expression of NFATc1 in 140 cases of CRC tissues and 35 corresponding adjacent tissues, as well as analyzed the correlation between NFATc1 expression levels and clinical stages. The role of NFATc1 in CRC metastasis and the molecular mechanisms were inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Likely, gene copy number, epigenetic alterations, and microenvironment-derived stimulant regulate PD-1 expression in human cancer cells. [32][33][34][35][36] As c-Fos binds to the AP-1-binding site and activates Pdcd1 transcription in tumor-infiltrating T cells, 29 Fos reduction was retrieved among the genes regulated in NIVO-treated colon cancer cells. Also, FOXO4 and FOXO3 were regulated by NIVO treatment in human colon cancer cells, mechanism previously reported for FOXO1 in antigen-specific CD8 +T cells during chronic lymphocytic choriomeningitis virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Likely, gene copy number, epigenetic alterations, and microenvironment-derived stimulant regulate PD-1 expression in human cancer cells. [32][33][34][35][36] As c-Fos binds to the AP-1-binding site and activates Pdcd1 transcription in tumor-infiltrating T cells, 29 Fos reduction was retrieved among the genes regulated in NIVO-treated colon cancer cells. Also, FOXO4 and FOXO3 were regulated by NIVO treatment in human colon cancer cells, mechanism previously reported for FOXO1 in antigen-specific CD8 +T cells during chronic lymphocytic choriomeningitis virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…[32] Besides, SNAI1 have a positive effect on the development and invasion of various tumors through inducing EMT. [33][34][35] In addition, IRX1, a member of the iroquois homeobox transcription factor family, has been identified as a tumor suppressor in several cancers, including lung adenocarcinoma, gastric cancer and invasive ductal carcinoma. [36][37][38][39] In our study, we found that high expressions of CDKN2A, SCD and SNAI1 were closely related to the poor prognosis, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Genes that appear to have interactions with the SNAI1 network in the STRING analysis have been reported to induce drug resistance, SNAI1 upregulation/activation, antitumor immune suppression and p53 antitumor mechanisms inhibition: the drug resistance genes set SORT1, 31–33 INPP4B, 32,34,35 PADI4, 36,37 AKT3, 38,39 EPAS1 (HIF2‐ α ), 40,41 TUBB2A, 42–44 ALOX5, 45 SPP1, 46 LMO4, 47,48 S100B 49 and JUN 50 ; and the immunomodulatory genes CCL23, 51 DPP4, 52,53 IL15, 54 MAF, 55 NFATC1, 56 STAT1, 57 CXCL10, 58 IRF1, 59 GZMB, 60 IDO1 61 and FoxP3, 62 except for MRC1, 63 PD‐L1 64 and BCL2, 65 which were upregulated by SNAI1, and PTEN, which was downregulated by SNAI1 65 . It seems that the upregulation of SNAI1 by these drug resistance and immunomodulatory genes is due to its synergetic effect in targeting and inhibiting p53 66 as well as the important role of SNAI1 in activating PI3K and ERKs signaling pathways responsible for developing intrinsic drug resistance and antitumor immune response suppression phenotypes 67 .…”
Section: Discussionmentioning
confidence: 99%